Non-invasive neuromodulation of the cervical vagus nerve in rare primary headaches - Villar-Martinez, Maria Dolores; Goadsby, Peter J. (Frontiers in Pain Research, 2023)
Primary headache disorders can be remarkably disabling and the therapeutic options available are usually limited to medication with a high rate of adverse events. We discuss the mechanism of action of non-invasive vagal nerve stimulation, as well as the findings of the main studies involving patients with primary headaches other than migraine or cluster headache, such as hemicrania continua, paroxysmal hemicrania, cough headache or short-lasting neuralgiform headache attacks (SUNCT/SUNA). The bibliographical search of low prevalence disorders such as rare primary headaches retrieves a moderate number of studies, usually underpowered. Headache intensity, severity and duration showed a clinically significant reduction in the majority, especially those involving indomethacin-responsive headaches. The lack of response of some patients with a similar diagnosis could be due to a different stimulation pattern, technique, or total dose. The use of non-invasive vagal nerve stimulation for the treatment of primary headache disorders represents an excellent option for patients with these debilitating otherwise refractory conditions, or that cannot tolerate several lines of preventive medication, and should always be considered before contemplating invasive, non-reversible stimulation techniques.